Kinerja Karyawan Ony Comp Malang: Peran Kepemimpinan, Pemberdayaan dan Motivasi Kerja - Nur Aini, Lilies; Nurtjahjani, Fullchis; Fany Novitasari, Ane; Dhakirah, Sanita (CV. Lafadz Jaya, 2023)
The success of company management is largely determined by the activities of utilizing human resources, where company managers must really pay attention to the attitudes, behavior, desires and needs of employees so that these employees can be encouraged to improve their performance. The aim of this research is to determine the relationship between leadership and empowerment on employee performance mediated by work motivation. The population in this study were 25 employees of Ony Comp Malang. This research uses a saturated sampling technique, so that the entire population becomes the sample in the research. The data collection method is through observation, interviews, questionnaires, while the data analysis method used is SEM-PLS with the help of SmartPLS software. The results of the research show that leadership has no effect on employee performance, empowerment has an effect on employee performance, leadership has an effect on work motivation, empowerment has an effect on work motivation, work motivation has an effect on employee performance, work motivation does not mediate the relationship between leadership and employee performance, and work motivation mediates the relationship empowerment on employee performance.